Isolation, culture mesenchymal stem cells derived from human placenta and differentiation to adipocye, osteoblast in vitro - Tu, Tran Cam; Son, Hoang Nghia (Academia Journal of Biology, 2012)
The presence within bone marrow of a population of mesenchymal stem cells (MSCs) able to differentiate into a number of different mesenchymal tissues, including bone and cartilage. Since then MSCs have been demonstrated in a variety of fetal and adult tissues, including bone marrow, fetal blood and liver, cord blood, amniotic fluid and, in adult peripheral blood. MSCs from these sources can be extensively expanded in vitro and when cultured under specific conditions retain their ability to differentiate into multiple lineages including bone, cartilage, fat, muscle, nerve, and stromal cells. There has been great interest in these cells both because of their value as a model for studying the molecular basis of differentiation and their therapeutic potential for tissue repair and immune modulation. However, MSCs are a rare population in these tissues. Here we tried to identify cells with MSC-like potency in human placenta. We isolated adherent cells from trypsin-digested term placentas and examined these cells for morphology, surface markers, and differentiation potential and found that they expressed several stem cell markers. We suggest that placenta-derived cells have multilineage differentiation potential similar to MSCs in terms of morphology and cell-surface antigen expression. The placenta may prove to be a useful source of MSCs.